2006
DOI: 10.1021/ac060830g
|View full text |Cite
|
Sign up to set email alerts
|

Label-Free Protein Biosensor Based on Aptamer-Modified Carbon Nanotube Field-Effect Transistors

Abstract: We have fabricated label-free protein biosensors based on aptamer-modified carbon nanotube field-effect transistors (CNT-FETs) for the detection of immunoglobulin E (IgE). After the covalent immobilization of 5'-amino-modified 45-mer aptamers on the CNT channels, the electrical properties of the CNT-FETs were monitored in real time. The introduction of target IgE at various concentrations caused a sharp decrease in the source-drain current, and a gradual saturation was observed at lower concentrations. The amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
503
0
4

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 651 publications
(513 citation statements)
references
References 43 publications
6
503
0
4
Order By: Relevance
“…[23,91] Drop casting, [95] dielectrophoresis, [96] and CVD growth [23,91,92,94,[97][98][99] have been employed for the fabrication of dispersed SWNT networks, although the latter approach is gaining greater acceptance owing to the ease of attaining bundle-free structures. Microlithography [92,94,98] and electron beam (e-beam) lithography [97] are typically employed to pattern source and drain contacts, although shadow mask metal evaporation is also used. [23,91] Figure 3a 4 and a 5 illustrate the typical gate configurations for SWNT-FET biosensors.…”
Section: Cnt Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…[23,91] Drop casting, [95] dielectrophoresis, [96] and CVD growth [23,91,92,94,[97][98][99] have been employed for the fabrication of dispersed SWNT networks, although the latter approach is gaining greater acceptance owing to the ease of attaining bundle-free structures. Microlithography [92,94,98] and electron beam (e-beam) lithography [97] are typically employed to pattern source and drain contacts, although shadow mask metal evaporation is also used. [23,91] Figure 3a 4 and a 5 illustrate the typical gate configurations for SWNT-FET biosensors.…”
Section: Cnt Characterizationmentioning
confidence: 99%
“…By integrating divalent cations and large Schottky contact areas, pM detection limits for DNA hybridization [92] and antibody-antigen binding [23,91] have been achieved. Aptamers (synthetic DNA or RNA strands designed to recognize amino acids, drugs, and proteins) were utilized to detect proteins, such as thrombin [94] and immunoglobulin E. [98] Their smaller size, as compared to protein receptors, was proposed to enhance the band structure changes in SWNT channel or Schottky barrier contact upon binding of analytes. A single sem-SWNT integrated FET was also utilized for detecting the pH changes down to a resolution of 0.1.…”
Section: Transistor Based Biosensorsmentioning
confidence: 99%
“…Maehashi et al reported an aptamer-modified carbon nanotube field-effect transistor (CNT-FET) for the detection of immunoglobulin E (IgE). 36 The introduction of IgE caused a significant I d decrease, whose magnitude was proportional to the concentration of IgE. The LOD achieved by this assay was 250 pM.…”
Section: Aptamer-based Sensing Approachesmentioning
confidence: 80%
“…Instead of using an antiIgE antibody to recognize the target IgE, an aptamer was chosen with the advantage of being insensitive to temperature and low cost. These interesting features explain the number of publications concerning IgE quantification with aptamers [10][11][12][13]. Other studies were also carried out, making use of surface plasmon resonance spectroscopy [14,15] and quartz crystal microbalance detection [15].…”
Section: Introductionmentioning
confidence: 94%